The Philosophical Scandal of the Wrong Kind of Religious Disagreement - Forrest, Peter (Sophia, 2009)
I argue for the following four theses: (1) The Dread Thesis: human beings should fear having false religious beliefs concerning some religious doctrines; (2) The Radical Uncertainty Thesis: we, namely most human beings in our culture at our time, are in a situation where we have to commit ourselves on the truth or falsity of some propositions of ultimate importance; (3) The Radical Choice Thesis: considerations of expected loss or gain do not always provide guidance as to how to commit ourselves on matters of religious doctrine that are both radically uncertain and of ultimate importance; (4) The Scandal Thesis: radical choice on matters of ultimate importance is neither good nor inevitable, but due to the collective failure of philosophers of religion. Then I consider some inadequate responses: playing the faith card; contra-Pascalian decision theory; spiritual chauvinism; that faith presupposes uncertainty; the older pachyderm; irony, subjectivity, relativism and non-cognitivism; tainted truth; and muddling through. Finally I submit that the way forward is quite simply to become better philosophers.